STRATEGI PENGEMBANGAN USAHA SPAREPART SEPEDA MOTOR DENGAN MENGGUNAKAN ANALISIS SWOT PADA TOKO ZIF JAYA GORONTALO - Lahmudin, Moh Rifaizal; M. Suyanto; Kartika Wijayanti, Yulyar; Rahmiyati, Nekky (Journal of Management and Innovation Entrepreneurship (JMIE), 2024)
This research discusses the business development strategy of Zif Jaya Gorontalo shop using SWOT analysis. Toko Zif Jaya Gorontalo is a business that focuses on selling motorcycle spare parts. The purpose of this research is to identify internal and external factors that affect the business, identify alternative business strategies that are effective for improving spare parts business performance, and determine the most appropriate strategy. The methods used include Business Model Canvas (BMC) to map the business model, SWOT analysis, IFAS and EFAS matrix, and economic analysis to determine the Break Even Point (BEP). The results showed that toko Zif Jaya Gorontalo store has dominant strengths compared to weaknesses, has significant strengths in product and service diversification, and strategic location advantages. The development strategy that can be used is to focus on capitalizing on internal strengths and external opportunities (S-O strategy). The development strategy is that Toko Zif Jaya Gorontalo can consider further utilizing its strategic location by conducting more aggressive promotions, improving customer service by using the latest technology, adding technicians by recruiting more employees to overcome limitations in services and operations.